Evaluation of the Strategic Approaches to Community Safety Initiative (SACSI) in Winston-Salem, North Carolina, 1998-2001 - Easterling, Doug ([Verlag nicht ermittelbar], 2008)
The purpose of this study was to perform an initial evaluation of key aspects of the Winston-Salem Strategic Approaches to Community Safety Initiative (SACSI). The research team administered a SACSI Process Questionnaire to the SACSI Core Team and Working Group during the fall of 2000. Part 1, SACSI Core Team/Working Group Questionnaire Data, provides survey responses from 28 members of the Working Group and/or Core Team who completed the questionnaires. Variables in Part 1 were divided into four sections: (1) perceived functioning of the Core Team/Working Group, (2) personal experience of the group/team member, (3) perceived effectiveness or ineffectiveness of various elements of the SACSI program, and (4) reactions to suggestions for increasing the scope of the SACSI program. The research team also conducted an analysis of reoffending among SACSI Offenders in Winston-Salem, North Carolina, in order to assess whether criminal behavior changed following the implementation of the Notification Program that was conducted with offenders on probation to communicate to them the low tolerance for violent crime in the community. To determine if criminal behavior changed following the program, the research team obtained arrest records from the Winston-Salem Police Department of 138 subjects who attended a notification session between September 9, 1999, and September 7, 2000. These records are contained in Part 2, Notification Program Offender Data. Variables in Part 2 included notification (status and date), age group, prior record, and 36 variables pertaining to being arrested for or identified as a suspect in nine specific types of crime.